The Occlusal Plane Inclination Analysis for Determining Skeletal Class III Malocclusion Diagnosis - Ardani IGAW; Wicaksono A; Hamid T (Dove Medical Press, 2020)
I Gusti Aju Wahju Ardani, Ageng Wicaksono, Thalca Hamid Orthodontics Department, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, East Java, IndonesiaCorrespondence: I Gusti Aju Wahju ArdaniDepartment of Orthodontics, Faculty of Dental Medicine, Universitas Airlangga, Jl. Prof. Dr. Moestopo 47, Surabaya, IndonesiaTel/Fax +62 31 5030255Email wahju_ardani@fkg.unair.ac.idIntroduction: The occlusal plane is very important in the stomatognathic and aesthetic dentofacial system. Manipulation of the occlusal plane plays an important role in class III malocclusion correction. For this reason, the strategy in establishing the diagnosis, prognosis and treatment plan becomes more complex, so a more comprehensive analysis of the occlusal plane inclination as a parameter of diagnosis is needed for more effective and efficient treatments.Aim: The aim of this study was to determine the comparison of occlusal plane inclination between class III and class I malocclusions and to knowing the correlation of occlusal plane inclination in class III malocclusions with the direction of facial growth.Materials and Methods: Samples were secondary lateral cephalograms collected at the Universitas Airlangga (UNAIR) Dental Hospital in October 2017– 2018. Cephalograms were traced using the OrthovisionTM software; then, the Mann–Whitney comparative statistical test (p< 0.05) was carried out followed by the canonical correlation test.Results: Differences in class III and class I malocclusions were found in the OP-AB and OP-FH angles. The OP-AB angle is the occlusal plane inclination which has the strongest correlation compared to others. OP-AB angle is strongly correlated with horizontal growth parameter, especially theSNB. The OP-AB angle is also correlated with vertical growth parameters: the Y axis and the Facial axis.Conclusion: The OP-AB angle is a parameter that can distinguish between class III and class I malocclusions. The OP-AB angle has a strong correlation with vertical and horizontal growth directions.Keywords: cephalometry, facial growth, class III malocclusion, occlusal plane